Phosphorus, soluble carbohydrates and the competition between two arbuscular mycorrhizal fungi colonizing subterranean clover - Pearson, J N (The New phytologist, 1994)
We investigated the competition between two arbuscular mycorrhizal fungi, Glomus sp. [isolate WUM 10(1)] and Scutellospora calospora [isolate WUM 12(3)] during the colonization of subterranean clover at four concentrations of soil phosphorus (P). When the clover seedlings were 4 wks old we collected data for plant growth, P uptake, mycorrhizal colonization and soluble carbohydrate status of the roots. The percent and total colonization by Glomus sp. was reduced to a much greater extent than S. calospora when the soil P status was increased. When both fungi were inoculated together, S. calospora was unaffected by the presence of Glomus sp. or the P status of the soil; Glomus sp., however, was reduced to a far greater extent when in the presence of S. calospora than compared to when it was inoculated alone, Associated with the decreases in colonization by Glomus sp., when inoculated alone, with S. calospara and with increases in the level of P applied to the soil, were decreases in the concentration of soluble carbohydrates within the root. We propose that root carbohydrates directly influence the outcome of competition between these two isolates during the colonization of subterranean clover